Computer modeling of embryonic mortality at crioconservation - Gorbunov, L. V.; Cherniavska, Ye. G. (Національна академія наук України; Інститут біохімії ім. О. В. Палладіна НАН України, 2016)
The purpose of the research was to determine the regularities of influence of mammalian embryos heterogeneity and effectiveness of cryoconservation steps on their viability by using the developed simulation model. The model is based on analytical expressions that reflect the main causes of embryonic mortality during in vitro and in vivo cultivation, crioconservation and embryo transplantation. Reduction of viability depends on a set of biological factors such as the animal special, donor and recipient state, quality of embryos, and of technological ones such as the efficiency of cryopreservation method, and embryo transplantation. Fulfilled computer experiment showed, that divergence of embryos viability depending on biological parameters variations changes in a range from 0 to 100%, whereas efficiency index of chosen technology has an inaccuracy about 1%. The comparative analysis of alternative technologies of embryos cryopreservation showed the maximum efficiency of stages of use of the cryoprotectant, freezing regime and in vitro and in vivo cultivation of biological object. The application of computer modeling gives an opportunity to reduce the range of embryos viability results, obtained in different experiments is many times, thereby to shorten the time, monetary costs and the slaughter of laboratory animals in obtaining reliable results.

Мета роботи — визначення закономірностей впливу гетерогенності ембріонів ссавців та ефективності етапів кріоконсервування на їхню життєздатність за допомогою розробленої імітаційної моделі. В основу моделі покладено аналітичний вираз, що відображає основні причини ембріональної смертності у процесі культивування в умовах in vitro та in vivo, кріоконсервування та трансплантації зародків. Зниження життєздатності залежить від низки біологічних факторів, зокрема виду тварини, стану донора і реципієнта, якості ембріонів, а також від технологічних — ефективності способів кріоконсервування і трансплантації ембріонів. Здійснений комп'ютерний експеримент показав, що розбіжність життєздатності ембріонів залежно від варіації біологічних параметрів змінюється від 0 до 100%, тоді як показник ефективності обраної технології при цьому має похибку близько 1%. Порівняльний аналіз альтернативних технологій кріоконсервування ембріонів свідчить про максимальну ефективність етапів застосування кріопротектора, режиму заморожування і культивування об’єкта в умовах in vitro та in vivo. Застосування комп’ютерного моделювання дає змогу знизити у багато разів розкид даних життєздатності ембріонів, отриманих у різних дослідах, і тим самим більш ніж на порядок скоротити час, зменшити грошові витрати та забій лабораторних тварин за одержання достовірного результату.
Комп'ютерне моделювання загибелі ембріонів за кріоконсервування
Keywords: cryopreservation; embryos; mortality; кріоконсервація; ембріони; смертність